PENGARUH PENGGUNAAN E-MODUL BERBASIS REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK KELAS VIII SMP NEGERI 8 PADANG - Azrianto, Afdhal (Jurnal Edukasi dan Penelitian Matematika, 2024)
Because it is one of the domains tested in the Minimum Competency Assessment (AKM), which is an alternative to the National Exam (UN), students nowadays must demonstrate proficiency in numeracy literacy. The aim of this research is to find out whether, in the TP 2023/2024, eighth graders at SMP Negeri 8 Padang were able to improve their skills more effectively by using RME-based e-modules instead of traditional course materials. A quasi-experimental design based on a nonequivalent posttest-only control group was used for the investigation. In the context of eighth grade at SMP Negeri 8 Padang, the results show that using e-modules based on RME improves students' numeracy literacy skills.Keywords – Numeracy literacy skills, E-Modules, Approach Realistic Mathematics Education